BS EN 4073. Aerospace series. Screws, pan head, hexalobular recess, coarse tolerance shank, medium length thread in alloy steel, cadmium plated. Classification. 1 100 MPa (at ambient temperature) / 235 °C. (22nd June 2023) - British Standards Institution,
No abstract available